2018
DOI: 10.1172/jci96060
|View full text |Cite
|
Sign up to set email alerts
|

TRAF4-mediated ubiquitination of NGF receptor TrkA regulates prostate cancer metastasis

Abstract: Receptor tyrosine kinases (RTKs) are important drivers of cancers. In addition to genomic alterations, aberrant activation of WT RTKs plays an important role in driving cancer progression. However, the mechanisms underlying how RTKs drive prostate cancer remain incompletely characterized. Here we show that non-proteolytic ubiquitination of RTK regulates its kinase activity and contributes to RTK-mediated prostate cancer metastasis. TRAF4, an E3 ubiquitin ligase, is highly expressed in metastatic prostate cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
68
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(73 citation statements)
references
References 71 publications
0
68
0
Order By: Relevance
“…Studies have confirmed that ubiquitination is an important posttranslational modification [19]. In clinical researches, ubiquitinated dysfunction could upregulate many oncogenic proteins that result in tumor formation [20][21][22].…”
Section: Discussionmentioning
confidence: 95%
“…Studies have confirmed that ubiquitination is an important posttranslational modification [19]. In clinical researches, ubiquitinated dysfunction could upregulate many oncogenic proteins that result in tumor formation [20][21][22].…”
Section: Discussionmentioning
confidence: 95%
“…Accumulating studies have demonstrated that TRAF4 interacts with several molecules to function in certain circumstances [25,26]. Thus, we speculated that TRAF4 may interact with some classical osteogenesis-related molecules to modulate the osteogenic differentiation of MSCs.…”
Section: Traf4 Diminishes the Expression Of Smurf2 To Modulate Osteogmentioning
confidence: 91%
“…Available human evidence indicates that gene amplification is the most common TRAF4 genetic alteration in cancers and that TRAF4 expression is ubiquitously elevated in many human cancers ( 196 – 204 ). This suggests that TRAF4 overexpression may play causal roles in cancer initiation, progression and metastasis.…”
Section: Traf4mentioning
confidence: 99%
“…In addition to the established IL-17A-TRAF4-ERK5 axis, a variety of potential TRAF4 -dependent oncogenic pathways have been suggested by studies of patient samples, cultured human cancer cells or their xenografts in immunodeficient mice. These include: (1) TRAF4-Akt/NF-κB-Glut1/HK2/RSK4/Slug in the proliferation and metastasis of lung and breast cancer cells as well as the migration and epithelial-mesenchymal transition (EMT) of hepatocellular carcinoma cells (HCC) ( 199 , 203 , 206 ); (2) TGFβ-TβRI-TRAF4-Smurf1/Smurf2/USP15-SMAD2/TAK1-N-cadherin/Fibronectin/Vimentin/SMA in the migration, EMT, and metastasis of breast cancer cells ( 200 , 207 ); (3) SRC3-TRAF4-mediated inhibition of the USP7-p53 interaction, leading to the loss of p53 deubiquitination/stabilization and thus the resistance to cytotoxic drugs and stress in breast cancer ( 208 ); (4) NGF-TrkA-TRAF4-Akt/p38-IL-6/Integrins/COX2 in the metastasis of prostate cancer cells ( 204 ); (5) TNFα-TRAF4/TRAF2-NF-κB1 in the survival and proliferation of breast cancer cells ( 209 ); (6) TRAF4-mediated up-regulation and nuclear translocation of β-catenin in the Wnt/β-catenin-cyclin D1/c-myc/Bcl-2/MMPs pathway that promote the growth and migration of OSCC and breast cancer cells ( 210 , 211 ); (7) TRAF4-mTOR-p70S6K-S6 in the proliferation of breast cancer cells ( 212 ); and (8) the TRAF4-phosphoinositide (PIP) interaction at tight junctions that favors breast cancer cell migration ( 213 ). It would be interesting to verify these TRAF4-dependent oncogenic pathways using in vivo models.…”
Section: Traf4mentioning
confidence: 99%